In situ assembled La0.8Sr0.2MnO3 cathodes on a Y2O3–ZrO2 electrolyte of solid oxide fuel cells – interface and electrochemical activity. Issue 101 (18th October 2016) - Li, Na; Ai, Na; Chen, Kongfa; Cheng, Yi; He, Shuai; Saunders, Martin; Dodd, Aaron; Suvorova, Alexandra; Jiang, San Ping
Abstract : Polarization can induce an LSM/YSZ interface which is electrochemically compatible with the one formed under high temperature sintering. Abstract : Formation of an intimate electrode/electrolyte interface is essential for solid oxide fuel cells (SOFCs). In this study, a comparative investigation has been undertaken to study the interface formation between a La0.8 Sr0.2 MnO3 (LSM) cathode and Y2 O3 –ZrO2 (YSZ) electrolyte by high temperature sintering and by cathodic polarization using EIS, SEM, AFM and HAADF-STEM techniques. The electrode/electrolyte interface formed by the conventional pre-sintering process is characterized by the formation of distinctive convex contact rings on the YSZ surface and such convex contact rings are due to the cation interdiffusion such as manganese species between LSM and YSZ. Similar to the thermally induced interface, the electrode/electrolyte interface can also be formed by electrochemical polarization for the in situ assembled LSM cathode on YSZ as well as on Gd2 O3 –CeO2 (GDC) electrolytes without pre-sintering at high temperatures. The polarization induced interface has smaller contact marks due to the much finer grain size of the as-prepared LSM electrodes. Detailed electrochemical impedance studies indicate that both thermally and polarization induced LSM/YSZ interfaces show comparable electrocatalytic activity and behaviour for the oxygen reduction reaction with similar activation energies. The present study clearly demonstrates the formation of effective electrode/electrolyte interfaces in SOFCs under the influence of cathodic polarization without high temperature sintering steps.